Evolution of microstructure and CO2 diffusion coefficient of compacted recycled aggregates during carbonation investigated by X-ray tomography. (3rd April 2023) - Hou, Yunlu; Lux, Jérôme; Mahieux, Pierre-Yves; Turcry, Philippe; Aït-Mokhtar, Abdelkarim
Highlights: Modifications of the microstructure due to carbonation seems to be limited to intra-granular porosity. The segmented 3D image allows determining the macroscopic diffusivity tensor. CO2 diffusion coefficient depends mainly on the inter-granular porosity network. Abstract: Recycled aggregates compacted in road layers are made of a majority of concrete aggregates which can mineralize atmospheric CO2 . Previous studies showed that carbonation modifies the microstructure of recycled concrete aggregates, but little information is available in the case of compacted recycled aggregates. Furthermore, carbonation kinetics depends on CO2 diffusion through the compacted material, which is linked its microstructure. This paper presents an investigation of the evolution of both microstructure and CO2 diffusion coefficient of compacted recycled aggregates during carbonation in two different environments by X-ray tomography. Segmented 3D images were analyzed to fully extract resolved pore structures. In addition, the CO2 diffusion coefficient variations were investigated by calculating the macroscopic diffusivity tensor in the segmented 3D images. We show that the numerical results are very similar to previous experimental results from gas diffusion tests and that the diffusivity coefficients can be estimated by using only the larger pore network (pore size > 5.5 µm). These findings suggest that nondestructive imaging approaches, such as micro-Computed Tomography (µCT), are a relevant alternative to experimental characterization methods.